2017
DOI: 10.1074/jbc.m117.814491
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of sphingosine-1-phosphate lyase protects insulin-secreting cells against cytokine toxicity

Abstract: Increasing evidence suggests a crucial role of inflammation in cytokine-mediated β-cell dysfunction and death in type 1 diabetes mellitus, although the mechanisms are incompletely understood. Sphingosine 1-phosphate (S1P) is a multifunctional bioactive sphingolipid involved in the development of many autoimmune and inflammatory diseases. Here, we investigated the role of intracellular S1P in insulin-secreting INS1E cells by genetically manipulating the S1P-metabolizing enzyme S1P lyase (SPL). The expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
110
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(126 citation statements)
references
References 66 publications
16
110
0
Order By: Relevance
“…The deficiency of SPL promotes tumor growth and survival [86][87][88]. In neurons [89][90][91][92][93][94][95] and pancreatic beta-cells [21] intracellular S1P is involved in cytotoxic effects (see below). The effects of S1P are mediated by cell surface receptors and by activation of intracellular targets [1][2][3].…”
Section: Sphingosine 1 Phosphatementioning
confidence: 99%
See 3 more Smart Citations
“…The deficiency of SPL promotes tumor growth and survival [86][87][88]. In neurons [89][90][91][92][93][94][95] and pancreatic beta-cells [21] intracellular S1P is involved in cytotoxic effects (see below). The effects of S1P are mediated by cell surface receptors and by activation of intracellular targets [1][2][3].…”
Section: Sphingosine 1 Phosphatementioning
confidence: 99%
“…Moreover the SK2-mediated formation of S1P in the nucleus has been associated with changes in the epigenetic signature of cells due to the ability of S1P to directly bind and inhibit the histone deacetylases HDAC1 and HDAC2 [100,101]. Finally, many studies reported calcium as a possible second messenger in the intracellular action of S1P [21,89,93].…”
Section: Sphingosine 1 Phosphatementioning
confidence: 99%
See 2 more Smart Citations
“…A b b r e v i a t i o n s : C o e n z y m e A : C o A ; s e r i n e palmitoyltransferase: SPT; 3-keto-Dihydrosphingosine: KDS; 3-ketodihydrosphingosine reductase: KDSR; dihydrosphingosine: dhSPH; dihydro ceramide: dhCer; (dihydro)ceramide synthase: CerS; (dihydro) ceramide desaturase: DES; DAG: diacylglycerol; phosphatidylcholine: PC; sphingomyelin synthase: SMS; sphingomyelinase: aSMase; ceramide kinase: CerK; ceramide-1P Cer-1P; ceramide-1P: phosphatase: C1PP, sphingosine: Sph; glucosylceramide synthase: G l u C e r ; a c i d -β -g l u c o s y l c e r a m i d a s e : a c i d -β -G l u C e r a s e ; galactosylceramide: GalCer; galactosylceramide synthase: GalCerS; galactosylceramide galactosylceramide: GalCer; ceramidase: GalCer ceramidase; glucosylceramide: GluCer; lactosylceramide: LacCer; ganglioside M3: GM3; ganglioside D3: GD3; ganglioside D2: GD2; globotriaosylceramide 3: Gb3; sphingosine kinase: SPHK; sphingosine-1-phosphate phosphatase: S1PP; sphingosine-1-phosphate lyase: S1PL; CoA synthase: CoAS; aldehyde dehydrogenase: ALDH. increasing number of scientific studies have now shown a neurotoxic effect of S1P [17] and a cytotoxic effect in pancreas β-cells [18]. A large number of extracellular signals or stimuli elevates intracellular Cer (heat shock, ionizing radiation, oxidative stress, tumor necrosis factor (TNF)-α, nitric oxide (NO), etc.)…”
Section: Sl Functionsmentioning
confidence: 99%